2022
DOI: 10.1101/2022.02.17.22271116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19-related Smell and Taste Impairment with Widespread Diffusion of SARS-CoV-2 Omicron Variant

Abstract: Background. The aim of this study was to estimate the prevalence of self-reported chemosensory dysfunction in a study cohort of subjects who developed a mild-to-moderate COVID-19 in the period from January 17, 2022 to February 4, 2022 (Omicron proxy period) and compared that with a historical series of patients tested positive for SARS-CoV-2 infection between March and April, 2020 (comparator period). Methods. Prospective study based on the sinonasal outcome tool 22 (SNOT-22), item sense of smell or taste and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Strikingly, loss of smell and taste was reported in 12% (median duration 2 days) and 23% (median duration 2.5 days), respectively ( 15 ). This feature has also been supported by US State Department of Health ( 16 ) and by others studies ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Strikingly, loss of smell and taste was reported in 12% (median duration 2 days) and 23% (median duration 2.5 days), respectively ( 15 ). This feature has also been supported by US State Department of Health ( 16 ) and by others studies ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 78%
“…Vihta et al ( 17 ) showed loss of smell and taste was found to be less common among Omicron compared to Delta cases (13% of Omicron cases, 34% of Delta cases, odds ratio 0.22, 95% CI: 0.21–0.23). Moreover, Boscolo-Rizzo et al ( 18 ), in a pre-printed version, presented data on a prospective study on mild-to-moderate symptomatic adult patients and reported that 24.6% of patients had smell alterations during the proxy Omicron period compared to 62.6% during the comparator period mainly driven by the delta variant ( p < 0.001). Finally, a recent report led by Maisa et al collecting 468 Omicron cases in different regions of France reported an 8.3% of anosmia ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous neurotropic agents, including parasites, bacteria and viruses, can reach the CNs via the olfactory nerve. [8,11] Other possibilities for neuroinvasion of SARS-CoV-2 are through hematogenous spread via either the blood-brain barrier (BBB) or the blood-cerebrospinal fl uid barrier (B-CSFB). [18] Coronaviruses cell entry depends on the viral spike (S) protein binding to cellular receptors and its priming by host cell proteases.…”
Section: Perspectivementioning
confidence: 99%
“…[6,7] Some research suggests that 48% of people carrying the original mutation of the novel coronavirus lost smell, and 41% had a loss of taste; these numbers decreased to 23% for loss of taste and 12% for loss of smell among omicron-infected patients. [8] Consequently, many people may not realize they have contracted COVID-19, since fewer experience cough, fever, or loss of taste or smell. A virus in the upper respiratory tract is associated with increased transmissibility, but with a less severe disease, exhibiting similarities with fl u strains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, only 11% of Australian COVID-19 patients reported sensory changes compared to 55% of European COVID-19 patients (13). A study comparing chemosensory dysfunction in a cohort of patients infected in January and February 2022 to those infected in March and April 2020 found that self-reported chemosensory dysfunction was significantly lower in those infected in 2022 (15); less than 25% of those infected in early 2022 reported altered sense of smell compared to more than 60% in early 2020. Similarly, an analysis of 12 reports of patients infected with COVID-19 during the Omicron wave had a pooled estimated of olfactory dysfunction of only 13% (14).…”
Section: Sensory Impact Of Covid-19mentioning
confidence: 99%